PERTIMBANGAN PENOLAKAN HAKIM DALAM PUTUSAN PERMOHONAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG OLEH PT. ADHIKARA PUTRA MANDIRI TERHADAP PT. BANYU TELAGA MAS: Judge’s Rejection of the Postponement of Debt Payment Obligations (PKPU) Filed by PT Adhikara Putra Mandiri Against PT Banyu Telaga Mas - Chaezarani, Salsabila; Sanusi, Heru Pringgodani (Faculty of Law, Universitas Trisakti, 2025)
In the judge's consideration, the judge rejected the request for Postponement of Debt Payment Obligations (PKPU) filed by PT Adhikara Putra Mandiri as a creditor against PT Banyu Telaga Mas as a debtor on the grounds that the elements of simple proof were not fulfilled. The question is whether Law Number 37 of 2004 which regulates Bankruptcy and Suspension of Debt Payment Obligations is in line with the rejection of the judge’s consideration in the PKPU application. This research uses a descriptive normative legal research methodology using secondary data derived from primary and secondary legal materials to then be analyzed qualitatively an deductively drawn conclusions. Because the requirements for filling a PKPU application are limited to what is mentioned in Article 222 of Law Number 37 of 2004 concerning bankruptcy and PKPU, therefore the results of this study can be concluded that judges clarity in the PKPU Process, fundamental evidentiary reqirements must be applied.